OPTIMIZATION OF NOVEL POLYMERIC NANOPARTICLE FORMULATIONS FOR INHALED TARGETED THERAPY OF LUNG DISEASES - Elbahr, Ramy Said Hussenien Mohamed (2024)
Pulmonary drug delivery is largely used in localised treatment of respiratory diseases. However, it suffers from various challenges, some of which could be overcome by the use of polymeric nanoparticles (NPs). Unfortunately, no inhalable powdered NPs-based therapeutic products have been translated to approved marketed products to date. Moreover, limited excipients, specifically polymers, have been deemed compatible with the inhaled route. Thus, this work aims to address the gap between the development of inhalable dry powdered polymeric NPs and their limited clinical translation. Poly (glycerol adipate) (PGA) has emerged as a green enzyme-synthesised biodegradable polymer which offers several advantages over traditional polymers in various drug delivery applications. These advantages include biodegradability, low toxicity, ease of preparation and scale up, and high functionalization. The aim of the current work is to test the aptness of PGA for pulmonary drug delivery application. However, the liquid nature of PGA and its low glass transition temperature (Tg) would limit the desired spray-drying of its NPs formulation into inhalable powders. Thus, modification of PGA will aim at obtaining more solid polymers with Tg values > 40oC. Yet, the preservation of biodegradability and safety of the modified polymers on lung cells should be confirmed. In the work described in chapter (2), PGA polymers were synthesised followed by modification with amino acids-N-acetamides using a Steglich esterification reaction at high % substitutions to obtain modified polymers with higher Tg values. Polymers were characterised using proton Nuclear Magnetic Resonance (1H NMR), Fourier-Transform Infrared Spectroscopy (FT-IR), Size Exclusion chromatography (SEC), Differential Scanning Calorimetry (DSC), and Water Contact Angle (WCA). Furthermore, polymers’ safety was evaluated on A549 lung cells using a MTT cell viability assay. The 1H NMR and FT-IR spectral analysis confirmed the successful synthesis of PGA polymers and their coupling to N-acetyl-tryptophan (NAT). The modified PGA-NAT polymers were solid in nature and showed positive correlation between their % substitution and Tg values which ranged between 40 – 63oC. Furthermore, PGA and PGA-NAT polymers demonstrated no toxicity on A549 lung cells. The work described in chapter (3) involved the optimisation of the modified polymers formulation into colloidally stable NPs using nanoprecipitation technique and excipients which are compatible with lung delivery. The NPs were characterised using Dynamic Light Scattering (DLS), morphologically examined using Transmission Electron Microscopy (TEM), and assessed for their safety on A549 lung cells using the MTT assay. The PGA-NAT NPs formulations showed spherical morphology with particle sizes between 40 – 250 nm, narrow size distribution, and negative ZP values between -5 to -45 mV. In addition, they showed no or minimal toxicity on A549 lung cells. In chapter (4), the hydrolytic and enzymatic degradability of the PGA-NAT polymers NPs were tested by incubation with different buffers and enzymes for various time intervals. The polymer degradation was evaluated by tracing the changes in its molar mass and chemical structure using SEC and 1H NMR analysis, respectively. Furthermore, the polymer NPs were loaded with a pair of fluorescent dyes with a fluorescence resonance energy transfer (FRET) effect followed by incubation with A549 lung cells in order to trace their cellular internalisation and degradability. The PGA-NAT NPs experienced minimal hydrolytic degradability with different buffers except for the 0.5 M HEPES buffer. However, the polymer NPs showed time-dependent enzymatic degradability with different enzymes in the following order: Lipase > Trypsin > Elastase > Esterase. In addition, the dyes-loaded polymer NPs showed time-dependent internalisation and degradation in the A549 lung cells. In conclusion, modification of PGA with NAT has elevated its Tg value. In addition, the modified polymers were successfully formulated into colloidally-stable NPs using lung compatible excipients. The developed polymers and their NPs formulations showed safety and biodegradability in lung cells. Thus, PGA-NAT polymeric NPs are promising delivery systems for the pulmonary route. Interestingly, future optimisation of the spray-drying of the PGA-NAT NPs formulations into inhalable powders can support their transition into clinical translation.